Clinical and histopathological features of adenomas of the ciliary pigment epithelium - Chang, Ying; Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose Adenomas of the ciliary pigment epithelium (CPE) are rare benign tumours which have mainly to be differentiated from malignant ciliary body melanomas. Here we report on a consecutive series of patients with CPE adenomas and describe their characteristics. Methods The retrospective hospital-based case series study included all patients who were consecutively operated for CPE adenomas. Results Of the 110 patients treated for ciliary body tumours, five patients (4.5%) had a CPE adenoma. Mean age was 59.0 ± 9.9 years (range: 46-72 years). Mean tumour apical thickness was 6.6 ± 1.7 mm. Tumour colour was mostly homogenously brown to black, and the tumour surface was smooth. The tumour masses pushed the iris tissue forward without infiltrating iris or anterior chamber angle. Sonography revealed an irregular echogram with sharp lesion borders and signs of blood flow in Color Doppler flow imaging. Ultrasonographic biomicroscopy demonstrated medium-low internal reflectivity and acoustic attenuation. In magnetic resonance imaging (MRI), the tumours as compared to brain were hyperintense on T1-weighted images and hypointense on T2-weighted images. Tumour tissue consisted of cords and nests of pigment epithelium cells separated by septa of vascularized fibrous connective tissue, leading to a pseudo-glandular appearance. The melanin granules in the cytoplasm were large and mostly spherical in shape. In four patients, the tumours were hyperpigmented. Tumour cells were large with round or oval nuclei and clearly detectable nucleoli. Conclusions These clinical characteristics of CPE adenomas, such as homogenous dark brown colour, smooth surface, iris dislocation and anterior chamber angle narrowing but no iris infiltration, segmental cataract, pigment dispersion, and, as compared to brain tissue, hypointensity and, as compared to extraocular muscles or lacrimal gland, hyperintensity on T2-weighted MRI images, may be helpful for the differentiation from ciliary body malignant melanomas.
Gesehen am 16.05.2019